On accuracy of the parameter of deep subcriticality determination by the Feynman method - V. M. Pavlovych; O. V. Pidnebesnyy (Ядерна фізика та енергетика)
This paper considers the application of the Feynman method of neutron noise analysis for determination of the deep subcriticality parameters for multiplying systems. In particular, it is shown that the selection of the width of the timeslots, for which the mean and variance of the number of the neutron detector counts should be determined, can significantly affect the accuracy of determination of prompt neutron decay constant (), espe-cially in case of deep subcriticality. Analysis is based on the Monte Carlo method of calculation (code MCNP) of the simple multiplying systems with different neutron multiplication factors. Simple method of determination of the optimum width of the timeslot, from the standpoint of  calculation increasing accuracy, near which it is ad-visable to build the experimental dependence of the dispersion to mean ratio for the determination of . It is also shown that bias estimates of  is determined not only by the finite sampling data, but also by the overlapping of neutron chains. That is, the intensity of the external neutron source must not exceed a certain value, which de-pends on the neutron multiplication factor.